Manak Salah Dalam Tradisi Lokal Di Desa Pakraman Julah Kabupaten Buleleng - I Gusti Agung Ayu Cintia Dewi (Kamaya: Jurnal Ilmu Agama, 2018)
Manak salah ritual is a ritual aimed at the community of Desa Pakraman Julah who gave birth to twins and boys or in Bali is often called the kembar buncing. Birth like this is considered unnatural so it must be exiled and made the ceremony. Implementation of manak salah ritual in Desa Pakraman Julah has uniqueness that has never been owned by other villages. The uniqueness is at the time of the implementation of the balik sumpah ritual at Pura Bale Agung, kembar buncing baby along with his parents were told to eat and drink like an animal, meaning that by behaving like an animal, it is expected to throw away the mistakes so far because it is considered unnatural born.